2019
DOI: 10.3390/molecules24244530
|View full text |Cite
|
Sign up to set email alerts
|

Much More Than a Pleasant Scent: A Review on Essential Oils Supporting the Immune System

Abstract: The augmenting acceptance and application of herbal medicine in prevention and treatment of diseases also involve the use of plant essential oils (EOs) through different routes of administration (aromatherapy). Scientific data supporting the efficacy of certain herbal products are continuously growing; however, the cumulative evidence is not always sufficient. The anti-inflammatory properties of EOs have been investigated more extensively and also reviewed in different settings, but so far, our review is the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 95 publications
0
50
0
9
Order By: Relevance
“…The effects of EOs have mainly been examined at the cellular level, including in monocytes, macrophages, and Th cells, in the context of the molecular impacts on cytokines or immunoglobulins. Only a few studies addressed possible genetic regulations and mechanisms [ 83 ]. Further research should focus on the genetic regulatory pathways involved.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of EOs have mainly been examined at the cellular level, including in monocytes, macrophages, and Th cells, in the context of the molecular impacts on cytokines or immunoglobulins. Only a few studies addressed possible genetic regulations and mechanisms [ 83 ]. Further research should focus on the genetic regulatory pathways involved.…”
Section: Resultsmentioning
confidence: 99%
“…A recent review synthesized available evidence on the immune function enhancing effects of essential oils and, in particular, results of studies about forest bathing were discussed, thus suggesting that even 2-h-long forest walks can be associated with a significant increase in Natural Killer (NK) cell count and activity and can augment the number of cytolytic molecules expressing cells, with such variations lasting for many days after the experience, both in healthy subjects and in individuals with cancer-related pain [61]. Some studies included in this review also showed an effect of forest bathing on serum levels of IL-8, IL-6, and TNFα [61]. These findings confirmed the main results of preclinical laboratory experiments [62].…”
Section: Immune System and Inflammationmentioning
confidence: 99%
“…A pre-treatment of allergic rhinitis models with α-pinene resulted in a significant reduction in clinical symptoms and inflammatory cytokine levels [149]. α-pinene also appears to exert moderate antimicrobial [150,151] and immune-modulating effects [61,62]. Finally, it has been shown that α-pinene binds to the GABA-A receptor, at the benzodiazepine binding site, thus prolonging GABAergic inhibitory signaling and suggesting an anxiolytic and sleep-enhancing effect [91].…”
Section: Pharmacological and Clinical Activities Of Pinenesmentioning
confidence: 99%
“…Closely related to nature and forest therapy is the field of aromatherapy. Preclinical and clinical research on the effects of certain bioactive compounds in essential oils, which are available in a large number of plants, has gained a boost and is increasingly published (116). Of particular interest are the effects of terpenes and terpenoids on the suppression of inflammatory and infection responses and the immunomodulatory properties of these compounds (117).…”
Section: Aromatherapymentioning
confidence: 99%